Identification of collaborative skills with serious games - Berdun, Franco (2014)
Collaborative skills are de ned as a subset of learned behaviors that involve people in interpersonal situations to get or keep strengthening the environment. If the collaborative skills of a group members is insu cient, individual behaviors might arise. These individual behaviors can negatively impact the performance of the group and prevent to achieve an adequate collaborative work. Collaborative skills are essential in the software development market, since the increasing complexity of applications causes the need of a coordinated work of teams to carry out the implementation of any project. (Párrafo extraído del texto a modo de resumen)